Integrating Socio-Demographic and Local Sustainability Indicators: Implications for Urban Health and Children’s Vulnerability in Henequén Neighborhood in Cartagena, Colombia - Irina P. Tirado-Ballestas; Jorge L. Gallego; Rohemi Zuluaga-Ortiz; Vladimir Roa-Pérez; Alejandro Silva-Cortés; María C. Sarmiento; Enrique J. De la Hoz-Domínguez (Urban Science, 2025)
This study integrates socio-demographic factors and local sustainability indicators to assess their implications for public health and social vulnerability in the Henequén neighborhood of Cartagena, Colombia. This historically marginalized community, primarily composed of women and displaced families, faces chronic exposure to environmental contaminants due to its past as a municipal landfill. Poor housing conditions, overcrowding, and inadequate access to water and sanitation services exacerbate health risks. Additionally, low educational attainment and limited economic opportunities contribute to cycles of poverty and illicit activities, disproportionately affecting children’s development. Using a cross-sectional and correlational approach, the study identifies key variables, such as housing conditions, access to basic services, and marital status, that shape social vulnerability. The findings are analyzed in the context of the United Nations Sustainable Development Goals (SDGs), particularly SDG 3 (Good Health and Well-being), SDG 6 (Clean Water and Sanitation), and SDG 11 (Sustainable Cities and Communities). The study highlights critical gaps in sustainability efforts and provides a framework for assessing local progress toward achieving these global development objectives.